Measurement of inelastic, single- and double-diffraction cross sections in proton-proton collisions at the LHC with ALICE - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (SPRINGER, 2013)
Measurements of cross sections of inelastic and diffractive processes in proton-proton collisions at LHC energies were carried out with the ALICE detector. The fractions of diffractive processes in inelastic collisions were determined from a study of gaps in charged particle pseudorapidity distributions: for single diffraction (diffractive mass M-X 3) sigma(DD)/sigma(INEL) = 0.11 +/- 0.03, 0.12 +/- 0.05, and 0.12(-0.04)(+0.05), respectively at root s = 0.9, 2.76, and 7 TeV. To measure the inelastic cross section, beam properties were determined with van der Meer scans, and, using a simulation of diffraction adjusted to data, the following values were obtained: sigma(INEL) = 62.8(-4.0)(+2.4)(model) +/- 1.2(lumi) mb at root s = 2.76 TeV and 73.2(-4.6)(+2.0)(model) +/- 2.6(lumi) mb at root s = 7 TeV. The single- and double-diffractive cross sections were calculated combining relative rates of diffraction with inelastic cross sections. The results are compared to previous measurements at proton-antiproton and proton-proton colliders at lower energies, to measurements by other experiments at the LHC, and to theoretical models.
Keywords: ELASTIC-SCATTERING; (P)OVER-BAR-P COLLISIONS; DISSOCIATION; ENERGY; PHYSICS; HARD